Digital agriculture drives carbon emission reduction in China - Wenyan, Yao; Chenghan, Li; Fangzhou, Lin (Frontiers in Environmental Science, 2025)
Agricultural activities markedly influence China’s goals of reaching carbon emission peaks and achieving carbon neutrality. This study explores the mechanisms by which digitalization in agriculture impacts carbon emissions and develops a corresponding analytical model. It examines the extent of agricultural digitalization and carbon emissions across 31 Chinese provinces from 2013 to 2020. Empirical findings demonstrate that digital agricultural practices significantly reduce carbon emissions within the agricultural sector, exhibiting notable spatial spillover effects. Additionally, green technological innovation and environmental regulatory frameworks act as crucial intermediary factors. The efficacy of digital agricultural technologies in reducing emissions varies across regions, showing stronger effects in inland provinces and areas primarily engaged in grain production, compared to non-grain-producing regions. The results contribute to the ongoing discussions on pathways for agricultural carbon mitigation in the context of rapid digital transformation in China’s agriculture. Furthermore, the study emphasizes the necessity of addressing agricultural environmental externalities and emphasizes the pivotal role of environmental regulations in reducing agricultural carbon emissions, aligning with China’s ecological governance objectives.